Aflatoxin B1 as a Threshold Concept of Uncertain Etiology of Chronic Kidney Diseases - Sada Abdullah Kareem; Rana M Hameed; Sami Abd AL-Redha; Hassanein Al-Khatt (Institute of Medico-legal Publications Pvt Ltd, 2021)
A case control study was conducted in karbala province to investigate aflatoxin B1 (AFB1) exposure among the chronic kidney disease (CKD) patients and healthy control. AFB1 level were measured qualitatively by Thin layer chromatography and quantitatively by high-performance liquid chromatography.The assessment of positive AFB1 samples were evaluated along with biomarkers of renal functions tests.The results showed that the investigated population were exposed to Aflatoxins. AFB1 was detected in 100% of uncertain CKD patients and 24%, 20% in certain CKD patients and healthy control respectively. The concentration ranges in serum samples were 0.68 –8.33 ng/mL for uncertain CKD patients, 1.21-5.60 ng/mL for certain CKD patients and 0.11- 1.30 ng/mL for healthy control. The un-certain etiology of CKD patients had a significant associations of decreasing GFR and increasing the levels of urea, creatinine with positive serum AFB1. This association was also highly interest with regard to potential interactions with Urea levels in the control group. The measurement of the AFB1 in serum samples of CKD patients and healthy control were indicated a long term exposure to the toxin which result in uncertain etiology of CKD. The effect of AFB1 exposure was confirmed through the assessment of the biochemical marker of renal tests. This study can be a good establish of a national AFs exposure monitoring programs. Also the study highlighted the needing to identify the pathogenesis of contribution AFB1 in the increasing number of uncertain CKD patients. Future study is encouraged to focus on broader areas which cover the whole of country.